2016
DOI: 10.1109/tasc.2016.2542001
|View full text |Cite
|
Sign up to set email alerts
|

Low AC Loss Inkjet-Printed Multifilamentary YBCO Coated Conductors

Abstract: Abstract-Impressive performance has been achieved in (RE)Ba2Cu3O7-δ (REBCO) coated conductors, but for many applications, the high cost and AC losses remain prohibitive. Inkjet printing methods combine scalability and low equipment cost with high resolution patterning, potentially addressing both issues by enabling the production of multifilamentary coated conductors without subtractive processing.The successful production of multifilamentary superconducting YBa2Cu3O7-δ (YBCO) structures by inkjet printing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…An advantage of Inkjet printing is that it permits patterning structures. Stripes of YBCO for AC-losses reduction have been successfully prepared on both RABiTs (Rolling-Assisted Biaxially Textured Substrates) [6] and ABAD (Alternating Beam Assisted Deposition) [7], [8] CC architectures. The ABAD method enables the use of a polycrystalline substrate, however it must be textured through a thick layer (> 1µm) of YSZ [9].…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of Inkjet printing is that it permits patterning structures. Stripes of YBCO for AC-losses reduction have been successfully prepared on both RABiTs (Rolling-Assisted Biaxially Textured Substrates) [6] and ABAD (Alternating Beam Assisted Deposition) [7], [8] CC architectures. The ABAD method enables the use of a polycrystalline substrate, however it must be textured through a thick layer (> 1µm) of YSZ [9].…”
Section: Introductionmentioning
confidence: 99%
“…A gap width of 100 µm was reported for the studies in [155] and good reproducibility of printed tracks was obtained. In 2016, Hopkins et al [157] demonstrated an inverse technique where printed narrow CeO 2 tracks effectively separated a subsequently overprinted REBCO layer. The authors used a low-fluorine YBCO precursor solution deposited on an SS/ABAD-YSZ/CZO substrate architecture and demonstrated functional filaments.…”
Section: Bottom-up Processesmentioning
confidence: 99%